VALIDITY OF TERMINATION OF EMPLOYMENT BY EMPLOYERS TO WORKERS DUE TO PROBLEMS ONLINE LOAN BILLING - Clarisa Permata Hariono Putri; Cindy Cornelia Kurniawan (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
Currently, workers are being terminated due to problems because online loan collection has occurred. This research aims to analyze the legality of termination of employment by employers against workers because of loan collection problems online from a labor law perspective. Research on this law is normative legal research with two approaches, namely statutory and conceptual approaches. Research results concluded that the termination of employment was due to problems with online loan collection can be declared legally valid if meets all three cumulative requirements to qualify for the cause termination of employment due to appropriate labor violations of Article 154 A paragraph (1) letter k Act on Concerning Manpower jo. Act on Job Creation.